A Clinical Prediction Score Including Trial of Antibiotics and C-Reactive Protein to Improve the Diagnosis of Tuberculosis in Ambulatory People With HIV. (6th January 2020) - Boyles, Tom H; Nduna, Matilda; Pitsi, Thalitha; Scott, Lesley; Fox, Matthew P; Maartens, Gary
Abstract: Background: The use of a "trial of antibiotics" as empiric therapy for bacterial pneumonia as a diagnostic tool for tuberculosis in people with HIV (PWH) was removed from World Health Organization (WHO) recommendations in 2007, based on expert opinion. Current guidelines recommend antibiotics only after 2 Xpert MTB/RIF tests (if available), chest x-ray, and clinical assessment have suggested that tuberculosis is unlikely. Despite this, a "trial of antibiotics" remains common in algorithms in low-resource settings, but its value is uncertain. C-reactive protein (CRP), which has been proposed as a "rule-out" test for tuberculosis, may be an objective marker of response to antibiotics. Methods: We performed a passive case-finding cohort study of adult PWH with a positive WHO symptom screen. All participants received antibiotics at first visit according to the local protocol and were reviewed to ascertain clinical response. Point-of-care CRP was measured at both visits. All patients had sputum tested with Xpert MTB/RIF Ultra (Ultra), and the reference standard was based on 2 sputum mycobacterial cultures. We explored multivariable prediction models (MPM) for tuberculosis based on 1 or 2 visits. Results: Seventy-five of 207 patients (36%) had confirmed tuberculosis. Clinical response to antibiotics after 2 days was a good predictor of disease. An MPM based on 2 visits, without CRP, had acceptable discrimination (c-statistic, 0.75) and calibration (goodness-of-fit P = .07). Addition of CRP after antibiotics improved the model moderately (c-statistic, 0.78). CRP at first visit was not an independent predictor of tuberculosis. Conclusions: In adult PWH seeking care for symptoms suggestive of tuberculosis, lack of response to antibiotics is a strong predictor of disease and is likely to be useful, particularly when access to Ultra is limited. CRP adds value when measured after antibiotics but is of limited value at first visit.